Comparison of crystallinity between natural hydroxyapatite and synthetic cp-Ti /HA coatings - Assis, Camila Molena de [UNESP]; Vercik, Luci Cristina de Oliveira [UNESP]; Santos, Márcio Luís dos [UNESP]; Fook, Marcus Vinícius Lia [UNESP]; Guastaldi, Antonio Carlos [UNESP] (ABM, ABC, ABPol, 2005)
Commercial purity titanium (cp-Ti), and some of its alloys are important materials in the medical field because of their excellent biocompatibility and mechanical properties. Recently a simple chemical method to induce bioactivity in these inert metallic materials was reported. In this work, the biomimetic chemical process has been used to modify the surface of cp-Ti with the formation of a deposit layer of apatite (a calcium phosphate compound). The main purpose was to study the influence of heat treatment on changes in crystallinity in the deposited phases. X-ray diffraction analysis and scanning electron microscopy showed that the apatite coatings heat treated between 400 and 600 °C were less crystalline, similar to biological apatites. Upon heat treatment at temperatures above 700 °C, the apatite coatings appeared more crystalline, and were a mixture of hydroxyapatite, octacalcium phosphate and magnesium phosphate.
Keywords: biomaterials; titanium; biomimetic process; hydroxyapatite